Goniothalamus lanceolatus extract inhibits the growth of human ovarian cancer cells through migration suppression and apoptosis induction - Nasibah Razali&, Norodiyah Othman&, Nur Hilwani Ismail, Nur Vicky Bihud&, Nor Hadiani Ismail&, Farida Zuraina Mohd Yusof& (Journal of Applied Pharmaceutical Science, 2021)
Several studies have revealed the medicinal potential of Goniothalamus lanceolatus (GL) for various diseases. This study aims to examine the effects of GL extracts on cell viability, migration, and apoptotic rate of chemosensitive and chemoresistant ovarian cancer cells. The dissolved GL leaf and root extracts in dichloromethane (DCM), hexane, and methanol were tested against PEO1 (chemosensitive) and PEO4 (chemoresistant) cell lines. MTT (3-(4,5-Dimethylthiazol2-yl)-2,5-Diphenyltetrazolium Bromide) assay was used to determine the cell viability after 24 hours exposure to various extract concentrations at two-fold serial dilutions (0–1,000 μg/ml). A scratch assay was used to examine cell migration. The Fluorescein isothiocyanate (FITC) flow cytometry was used to observe cell apoptosis. The results showed that GL leaf and root extracts inhibit the viability of PEO1 and PEO4 cells in a doseâ€‘dependent manner. The lowest 50% inhibitory concentration values for PEO1 were 31.40 ± 0.77 μg/ml in methanol root extracts while they were 22.02 ± 0.52 μg/ml for PEO4 in DCM leaf extracts. Cell migration rate was suppressed at 18.65% in PEO1 and 16.73% in PEO4 after 72 hours treatment compared to the untreated cells. The extract caused high percentages of early apoptosis in PEO4 (26.5%) compared to PEO1 (2.67%) after 48 hours treatment. Significant inhibitory effects of GL extracts on cell viability, cell migration, and apoptosis in both cell lines suggest its potential as a chemotherapeutics candidate for ovarian cancer. However, further downstream studies are needed to evaluate the cellular mechanisms.
Keywords: Goniothalamus lanceolatus, cytotoxicity, apoptosis, ovarian cancer cell line, chemosensitive, chemoresistance.